Design of green zinc‐based thermal stabilizers derived from tung oil fatty acid and study of thermal stabilization for PVC. Issue 14 (15th December 2016) - Li, Mei; Zhang, Jinwen; Xin, Junna; Huang, Kun; Li, Shouhai; Wang, Mei; Xia, Jianling
ABSTRACT: In this study, a new type of mixed calcium (Ca) and zinc (Zn) thermal stabilizers was prepared and evaluated for poly(vinyl chloride) (PVC) thermal stabilization. The mixed stabilizers were based on the Ca and Zn salts of polycarboxylic acid derived from eleostearic acid—the dominant fatty acid of tung oil fatty acids. Eleostearic acid was converted to a 21‐carbon diacid (C21DA) and a 22‐carbon triacid (C22TA), respectively, which were subsequently turned into calcium (Ca) and zinc (Zn) salts. Thermal stability of PVC compounds was examined by thermogravimetric analysis (TGA), discoloration test, Congo red test, and thermal decomposition kinetics. In comparison, commercial mixed Ca/Zn thermal stabilizers composed of stearate salts (CaSt2 /ZnSt2 ), were employed as controls. Because the salts of C21DA, C22TA and stearate have different metal contents, thermal stabilization effects were compared on the basis of both equal salt weight and equal metal ion content. It was noted that under both cases the long‐term thermal stability of the PVC samples followed the order of C21DA‐Ca/C21DA‐Zn > C22TA‐Ca/C22TA‐Zn > CaSt2 /ZnSt2 . The results suggest that the mixed Ca/Zn salts based on tung oil‐derived polycarboxylic acids have higher metal ion contents and cycloaliphatic structures and can effectively improve the thermal stability of PVC. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44679. Abstract :